TRANSLATION TECHNIQUES USED BY STUDENTS IN TRANSLATING ENGLISH NEWS ITEMS - Lestiyanawati, Rochyani; Hartono, Rudi; Sofwan, Ahmad (English Education Journal, 2014)
Due to the different aspects of the source language and the target language, there are some techniques involved in the translation process in order to achieve the equivalence of the translated works. This study is aimed at analyzing the translation techniques as proposed by Molina and Albir (2002) used by the sixth semester students of the English Department in translating news item texts from English into Indonesian. It also measures the translation quality related to the aspect of accuracy, clarity, and naturalness. And the last, it implies the studentsâ problems in translation. The findings indicate that, after analyzing and interpreting 225 sentences, literal translation is dominantly used as a technique in translating the source text with the highest used technique in which 149 of 225 sentences applied the technique. In relation to the translation quality, 155 sentences were found as accurate, 172 sentences were clear and 164 sentences were natural with the scoring rate of 2.1, 2.3, and 2.25 points in average. The questionnaire and interview result revealed that incommunicative or incorrect translation happened due to studentsâ unawareness about the context and the lack of the adequate knowledge about it. Some students also had less understanding about translation techniques.